EUROPEAN UNION FINANCIAL SUPPORT (Third Sector Social Economic Review, 2017)
European Union which is an example of cultural, economic and political integration and has 28 members has to be in the position of providing the continuity and a sustainable development since its foundation. It has been observing the economic and social developments of its members in terms of political, cultural and economic dimensions and using the financial intermediaries like credits and grants to balance their levels of international development. These intermediaries have been implemented on different programs for members, candidates and third countries.
Keywords: European Union; European Union Financial Support; Pre-accession Assistance (IPA); Cohesion Fund; European Investment Bank